Glucose-6-phosphate dehydrogenase deficiency in genetic resistance to malaria: a systematic review and meta-analysis (Research, Society and Development, 2022)
Several studies have been conducted aiming to detect the variety of genetic markers associated with malaria resistance. This work aimed to describe the relationship of glucose-6-phosphate dehydrogenase deficiency in host resistance to Plasmodium spp. To this end, a systematic review with meta-analysis was performed, following PRISMA guidelines. The search strategy was done in Medline via Pubmed, Science Direct, Lilacs, Scopus and Google academic. Risk of bias was used to evaluate each selected article using the Joanna Briggs Institute Critical Appraisal Checklist. Subsequently, together, the papers were evaluated using Egger's Test. In total, 638 articles were found. Of these, 26 participated in the qualitative synthesis and 15 in the quantitative. Of the 26 studies, 18 reported a relationship between enzyme deficit and malaria resistance. As for the results of the meta-analysis, it was found that G6PD deficiency may be associated with an individual's resistance to develop malaria, especially in Asians and Africans. Therefore, the results of this article may help in the development of new therapeutic strategies for this disease, benefiting public health worldwide.